2020
DOI: 10.1016/j.jenvman.2020.110603
|View full text |Cite
|
Sign up to set email alerts
|

Urban green infrastructure: A review on valuation toolkits from an urban planning perspective

Abstract: As a response to increasing urbanization and changing weather and climatic patterns, urban green infrastructure (UGI) emerged as a concept to increase resilience within the urban boundaries. Given that implementing these (semi-) natural solutions in practice requires a clear overview of the costs and benefits, valuation becomes ever important. A range of decision-support tools for green infrastructure and ecosystem services exist, developed for various purposes. This paper reviews the potential of 10 shortlist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(73 citation statements)
references
References 45 publications
0
49
0
1
Order By: Relevance
“…We have taken a note of the climate-forming and climate-regulating functions of green spaces [17,18] and their ability to qualitatively affect the ecological conditions of the city [1,19,20], accompanied by changes in vegetation phenology and the increase of the growing period in urban conditions [21]. Also we have taken into account the methodological methods of research on urbanization of territories [22], recommendations and guidelines for assessing green infrastructure [23], mechanisms for increasing the ecological efficiency of cities through the development of the industrial structure [24], including electricity [25], the development of public-private partnerships to create infrastructure of urbanized areas [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have taken a note of the climate-forming and climate-regulating functions of green spaces [17,18] and their ability to qualitatively affect the ecological conditions of the city [1,19,20], accompanied by changes in vegetation phenology and the increase of the growing period in urban conditions [21]. Also we have taken into account the methodological methods of research on urbanization of territories [22], recommendations and guidelines for assessing green infrastructure [23], mechanisms for increasing the ecological efficiency of cities through the development of the industrial structure [24], including electricity [25], the development of public-private partnerships to create infrastructure of urbanized areas [26].…”
Section: Methodsmentioning
confidence: 99%
“…Efficient planting of greenery in urban infrastructure is not cheap. But, as the work of domestic and foreign researchers shows, the solution to this problem is also possible [13,23,26]. Residents are ready to pay for improving the quality of the urban environment and its aesthetics.…”
Section: Itse-2020mentioning
confidence: 99%
“…According to the high-frequency keyword analysis and keyword cluster analysis in the previous sections, there are many studies that consider environmental and social benefits, as well as the valuation is often defined in biogeophysical terms. Although it is widely recognized that green infrastructures can influence several economic outcomes (De Groot et al, 2010;Kim & Song, 2019;Van Oijstaeijen et al, 2020), the absence of co-occurring keywords and clustering information related to economic benefit, indicates a lack of economic related research. A systematic review found that the economic valuation practices at green infrastructure are rare, leading to uncertainty of economic benefit and impact (Van Oijstaeijen et al, 2020).…”
Section: Spatial Scalementioning
confidence: 99%
“…Integrating the (bio-)physical dimensions with the on socio-cultural, institutional, and political conditions lead also to identify a series of barriers for G&BI uptake such as the lack of economic and social evaluation and the lack of integration with other urban (or spatial) dimensions. If some authors argue that economic value with its benefits and appropriate finance methods should be introduced to develop credible business projects for informed decision-making of local authority [16], others maintain that economic evaluation of ecosystem services and G&BI impacts lead to the commodification of fundamental non-renewable resources undermining their sustainability and equity dimension [17]. The adoption of a bioregional "scale" and approach can contribute to overcome this dichotomy linking the ecological dimension to the local economic dimension.…”
Section: Exploring Social-contratcs For Green and Blue Infrastructuresmentioning
confidence: 99%